A pediatric case of common lymphatic malformation in the floor of the mouth successfully treated with the Kampo medicine, Eppikajutsuto. Issue 4 (July 2022) - Tamura-Sugiyama, Tomoko; Noguchi, Tadahide; Tsukimura, Hisae; Satake-Ozawa, Michiko; Watanabe, Hideki; Oyatsu, Yukio; Mori, Yoshiyuki
Abstract: Common lymphatic malformations (LMs) are routinely treated with sclerotherapy or surgical excision. However, treatment using traditional herbal therapy, i.e., Kampo, has recently been reported in Japan. Herein, we report a case of pediatric LM on the floor of the mouth, which was successfully treated with Kampo medicine known as Eppikajutsuto (TJ-28). A 4-year-old boy was referred to our department by the Pediatric Surgery department for swelling in the right floor of the mouth which had been present since birth. An elastic soft and mobile mass on the floor of the mouth, and left lateral deviation of the tongue were observed. However, there were no issues with swallowing and speech. Magnetic resonance imaging (MRI) showed a multilocular mass on the right floor of the mouth; T1- and T2-weighted images showed low and high signal intensities, respectively. Considering the possibility of spontaneous resolution over time, we decided on long-term observation without treatment. Five years after our initial consultation, the patient presented with rapidly worsening intraoral swelling due to infection. Following treatment with antibiotics, we prescribed Eppikajutsuto (TJ-28) for a period of one year. During this treatment period the intraoral and submandibular swelling decreased, and the lateral deviation of the tongue improved. Follow-up MRI scans showed a marked decrease in contrast effect, reduced swelling, and improvement in tongue deviation. Follow-up of the patient by our department is ongoing. The treatment with Eppikajutsuto (TJ-28) is non-invasive and should be further evaluated as an effective treatment for pediatric LMs.